2011
DOI: 10.1038/embor.2011.46
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3A can activate the DNA damage response and cause cell‐cycle arrest

Abstract: Human apolipoprotein-B mRNA-editing catalytic polypeptidelike 3 (APOBEC3) proteins constitute a family of cytidine deaminases that mediate restriction of retroviruses, endogenous retro-elements and DNA viruses. It is well established that these enzymes are potent mutators of viral DNA, but it is unclear whether their editing activity is a threat to the integrity of the cellular genome. We show that expression of APOBEC3A can lead to induction of DNA breaks and activation of damage responses in a deaminase-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
236
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(259 citation statements)
references
References 22 publications
18
236
5
Order By: Relevance
“…Overexpressed Heterologous A3A Is Genotoxic, whereas Upregulated Physiologic A3A Is Safely Expressed-A3A overexpression has been reported to be genotoxic (22,23,26). To characterize the extent of A3A toxicity, we employed a doxycycline-inducible system to regulate A3A expression levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overexpressed Heterologous A3A Is Genotoxic, whereas Upregulated Physiologic A3A Is Safely Expressed-A3A overexpression has been reported to be genotoxic (22,23,26). To characterize the extent of A3A toxicity, we employed a doxycycline-inducible system to regulate A3A expression levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, A3A has also been shown to be genotoxic under conditions of overexpression (22,23,26) and to mutate genomic DNA (24,25). CD14 ϩ cells are known to express high levels of A3A upon type I IFN induction (4,6,7), suggesting that these cells must either have a mechanism for regulating A3A activity or be subject to its genotoxic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, we reported that A3A expression can induce DNA breaks and activate the cellular DNA damage response (DDR) in a deaminasedependent fashion. 31 The DDR induced by A3A was revealed using antibodies generated to specific phosphorylation marks on DNA damage/repair proteins (such as the histone variant H2AX), 32 and DNA breaks were detected using the terminal deoxynucleotidyl transferase dUTP nick end-labeling (TUNEL) assay. In addition, using a UNG inhibitor (UGI), we demonstrated that UNG activity is required for both A3A-induced DNA breaks and activation of the DDR, suggesting that DNA damage signaling occurs as a consequence of cellular processing of A3A-induced uracil lesions.…”
Section: Evidence For Apobec3-mediated Deamination Of Cellular Dnamentioning
confidence: 99%